Students with Mild Mental Retardation Participating in Recess - Lucas, Matthew D. (Journal of the American Academy of Special Education Professionals, 2011)
The participation of a student with mild mental retardation in recess can often be both challenging and rewarding for the student and teacher. This paper will address common characteristics of students with mild mental retardation and present basic solutions to improve the experience of these students in the recess setting. Initially the definition and prevalence of the disability will be presented. This will be followed by a discussion of the disability for an individual in the classroom, including appropriate teaching methods and lastly possible challenges and solutions for children with mild mental retardation in the recess setting. Lastly, specific methods of proactively including a student with mild mental retardation in a basketball-related recess activity will be discussed.